Identification of Stenotrophomonas maltophilia in Blood Cultures by Fluorescence in Situ Hybridization. Issue 6 (8th November 2021) - Asaadi, Hanieh; Tajbakhsh, Saeed; Naeimi, Behrouz; Gharibi, Omid
Abstract : Background: Stenotrophomonas maltophilia is a serious causative agent for bacteremia. Rapid identification of S. maltophilia in blood cultures is important to enable a satisfactory pathogen-based antibiotic therapy at an early stage. The aim of this study was to evaluate fluorescence in situ hybridization (FISH) for the identification of S. maltophilia in blood culture specimens. Methods: Three hundred positive blood culture specimens were examined by both FISH and conventional laboratory methods for the identification of S. maltophilia . The results of FISH were compared with the results of the conventional methods. Results: By conventional cultural and biochemical methods, S. maltophilia was identified in 47 blood culture specimens. Fluorescence in situ hybridization identified S. maltophilia in 46 of these 47 S. maltophilia –positive blood cultures. Thus, the sensitivity and specificity of FISH were 97.9% and 100%, respectively. Conclusions: Our findings suggest that FISH is a suitable method for the identification of S. maltophilia in blood cultures.